Genetic inhibition of flowering differs between juvenile and adult Citrus trees - Munoz-Fambuena, Natalia; Nicolás-Almansa, M.; Martínez-Fuentes, Amparo; Reig, Carmina; Iglesias, Domingo J.; Primo-Millo, Eduardo; Mesejo, Carlos; Agustí, Manuel (Oxford University Press, 2020)
Background and Aims In woody species, the juvenile period maintains the axillary meristems in a vegetative stage, unable to flower, for several years. However, in adult trees, some 1-year-old meristems flower whereas others remain vegetative to ensure a polycarpic growth habit. Both types of trees, therefore, have non-flowering meristems, and we hypothesize that the molecular mechanism regulating flower inhibition in juvenile trees is different from that in adult trees.